A rare case of giant occipital encephalocele with craniosynostosis - Dasgupta, Sibaji; Saha, Suniti Kumar; Baranwal, Sunil; Banga, Manpreet Singh; Sandeep, BV (Asian Journal of Medical Sciences, 2016)
Encephalocele and craniosynostosis are known separate entities found clinically. While searching for a causal association between them, there has been a proposed justified hypothesis. Yet the two conditions are very rarely found in association. We have happened to find such a rare case which we treated and followed up for establishing the proposed theory of association between the two clinical entities. Asian Journal of Medical Sciences Vol.7(4) 2016 98-100